Fiscal prudence: It's all in the timing - Estimating time-varying fiscal policy reaction functions for core EU countries - Tino Berger; Tore Dubbert; Ruben Schoonackers (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2021)
When estimating fiscal policy reaction functions (FRF), the literature has well recognized the importance of non-linearities. However, there is yet very little attempt to formally test for the presence and potential sources of a non-linear fiscal responsiveness. In this paper we address this gap by formally adressing model specification of the FRF in a panel of five EU countries. Employing a Bayesian stochastic model specification search algorithm, we provide formal evidence for time-varying fiscal prudence over the last 50 years. The primary balance responsiveness exhibits smooth but significant variation over time and thus confirms the necessity of a non-linear model. Moreover, the extended results show that dynamics can be partially linked to the interest rate growth differential and the level of public debt itself. However, no clear evidence is found in favor of the fiscal fatigue proposition.
Keywords: 330